Dietary Intakes of Folic Acid During Pregnancy Determines Maternal Re-Set of Metabolism Post-Birth in Wistar Rat Dams (FS08-06-19). (13th June 2019) - Pannia, Emanuela; Yang, Neil; Ho, Mandy; Hammoud, Rola; Kubant, Ruslan; Chatterjee, Diptendu; Pausova, Zdenka; Anderson, G Harvey
Abstract: Objectives: Nutrition during pregnancy alters the "re-set" of maternal metabolism and in turn the mother's metabolic phenotype later in life. Folic acid (FA, synthetic folate) consumed at intakes above requirements during pregnancy by rats leads to increased weight gain and altered DNA methylation in central and peripheral pathways regulating food intake. The objectives of this study were to examine the effects of intakes below and above FA dietary requirements on the re-set of energy metabolic pathways in Wistar rat mothers early post-birth. Methods: Pregnant Wistar rats ( n  = 12/group) were fed an AIN93G diet with 5 levels of FA: 0X, 1X (control, 2 mg FA/kg), 2.5X, 5X or 10X. Dams were fed 1X-FA during lactation up to 1-week post-weaning (PW) when maternal metabolism is thought to re-set to homeostasis and then terminated. Weekly body weight, food intake, expression of hypothalamic food-intake neurons, mRNA and protein expression of folate-related and energy metabolic genes, and glucoregulatory hormones were measured. The homeostatic model assessment of insulin resistance (HOMA-IR) was used as a surrogate index of insulin resistance. Results: Below (0X) and above (5X and 10X) FA requirements during pregnancy suppressed expression of hepatic folate metabolism (methyltetrahydrofolate (MTHF) reductase, and methionine synthase; P  < 0.05) genes and led to higher 5-MTHF ( P  < 0.005) in blood compared to control suggesting dysregulation of 1-carbon pathways. Dams fed 0X- and 5X-FA also had higher plasma insulin and HOMA-IR than controls and changes in glucose and lipid metabolism-regulating genes in muscle (Glucose transporter-4, and Peroxisome-proliferator activated receptors; P  < 0.05) but not liver or adipose at 1-week PW. The diets did not affect expression of hypothalamic food intake neurons nor body weight or food intake of the dams from birth to 1-week PW. Conclusions: FA below (0X) or above (5X, 10X) requirements during pregnancy induce dysregulation of 1-carbon pathways and delay re-set of energy metabolic pathways in Wistar rat dams by 4-weeks after birth, potentially programming long-term negative metabolic effects. Funding Sources: This research was supported by: Canadian Institute of Health Research, Institute of Nutrition, Metabolism and Diabetes (CIHR-INMD); EP supported by NSERC Alexander Graham Bell Canada Graduate Scholarships-Doctoral Program (CGS D).